SIKAP MAHASISWA TERHADAP PESAN PENGINGAT DONOR DARAH DENGAN TEKNOLOGI SMS GATEWAY - Sari, Ayulia Fardila (JURNAL MEDIA KESEHATAN, 2015)
According to the World Health Organization (WHO) blood supply recommendation,Indonesia has 2.5 million blood bags less than it is needed. The majority of Indonesian peoplehave already had mobile phones and thus favorable for the application of short message service(SMS). It is feaseable to use SMS in order to improve donor motivation. This study would like toevaluate students' attitude toward blood donor's message reminder using SMS from the BloodDonors Directory, Faculty of Medicine, Gadjah Mada University. It was a quantitative study withcross-sectional design. Undergraduate medical students recorded in the database of Blood DonorsDirectory Faculty of Medicine, Gadjah Mada University were chosen as the study population.Simple random sampling was applied to choose the subjects. This study used the framework ofTechnology Acceptance Model (TAM) and data were analyzed using Partial Least Square basedStructural Equation Modelling (SEM). Attitude of blood donor's message reminder significantlyinfluenced perceived ease of use and perceived usefulness of SMS technology. Attitude of blooddonor's message reminder significantly influenced perceived entertainment, irritation, as well ascredibility of message content. No significantly influenced by perceived informative. Theintention to donate blood were significantly influenced by the attitude of blood donor's messagereminder. Students' attitude in donating blood was positively influenced by good perceptionabout ease of use and usefulness of SMS technology. It was also positively influenced by positiveperception to entertaining and credible messages, as well as negative perception to irritatingmessages. The positive attitude towards donor's message reminder would support the intention tobehave as blood donors.